Profiles of subjective well-being in patients with chronic back pain: contrasting subjective and objective correlates - Wettstein, Markus; Eich, Wolfgang; Bieber, Christiane; Tesarz, Jonas (Pain medicine, 2019)
AbstractObjective. The detrimental impact of nonspecific chronic low back pain (CLBP) on quality of life is well known. However, patients with CLBP represent a